Stress testing market risk of German financial intermediaries - Alexander Falter; Michael Kleemann; Lena Strobel; Hannes Wilke (Deutsche Bundesbank, 2021)
The macroprudential market risk stress test presented in this paper proposes a framework to assess the vulnerability of the German financial system with respect to market price shocks, focusing on banks, insurers and investment funds in a consistent manner. A common market risk scenario is translated into price declines for individual financial assets and into incurred losses at the level of individual financial intermediaries. We illustrate our approach with two technical scenarios, derived as percentiles of historic market price movements, representing (i) a significant shock in risk premiums triggering repricing of assets considered risky and (ii) a shock in the yield curve, implying sharp increases in the risk-free rates. Moreover, our approach takes into account specificities in the transmission of market risk to individual financial intermediaries. This includes for banks the calculation of market losses according to the holding purpose and accounting treatment of portfolios. For insurers, adjustments of solvency capital requirements are considered. Meanwhile, second-round amplification and spill-over effects on security and fund share prices are discussed for investment funds due to their high interconnectedness and their susceptibility to redemptions which might trigger asset liquidations.
Keywords: C53; G21; G22; G23; 330; Stress testing; market risk; financial intermediaries; financial stability